Characterization of Atypical Enteropathogenic Escherichia coli Strains Harboring the astA Gene That Were Associated with a Waterborne Outbreak of Diarrhea in Japan - Yatsuyanagi, Jun (American Society for Microbiology, 2003)
The virulence traits of the Escherichia coli strain associated with a waterborne diarrhea outbreak were examined. Forty-one of 75 students (ages 12 to 15) in Akita Prefecture, Japan, showed clinical symptoms. Seven E. coli Ouk:K-:H45 isolates were isolated from the patients as the causative agent of this outbreak. One isolate (EC-3605) showed the presence of E. coli attaching-and-effacing (eaeA) and enteroaggregative E. coli heat-stable enterotoxin-1 (astA) genes and the absence of Shiga toxin (stx1 and stx2) genes. A polymorphic enteropathogenic E. coli (EPEC) adherence factor plasmid was detected in EC-3605 with a major structural gene deletion and a regulatory gene frameshift mutation, revealing that EC-3605 represents an atypical EPEC strain harboring the astA gene. The role that atypical EPEC strains harboring the astA gene play in human disease is unclear. Our results, along with those of others, present a possibility that these strains comprise a distinct category of diarrheagenic E. coli and that astA affects the age distribution of atypical-EPEC infection.